Canadian Annual Review of Politics and Public Affairs 2007 - Mutimer, David (Book collections on Project MUSE., 2014)
The Canadian Annual Review of Politics and Public Affairs is an acclaimed series that offers informed commentary on important national events and considers their significance in local and international contexts. This latest instalment covers a year of dramatic activity in provincial.